Factors associated with the quality of life of subjects with Parkinson's disease and burden on their caregivers - M. Rodríguez-Violante; A. Camacho-Ordoñez; A. Cervantes-Arriaga; P. González-Latapí; S. Velázquez-Osuna (Neurología (English Edition), 2015)
Introduction: Parkinson's disease affects the quality of life of the individual with the disease in addition to creating a burden on the caregiver. Factors related to these effects include motor and non-motor aspects of the disease, as well as traits inherent to the caregiver. Methods: We evaluated subjects with Parkinson's disease using the following instruments: Quality of Life Questionnaire PDQ-8, Movement Disorders Society Unified Parkinson's Disease Rating Scale part I to IV (MDS-UPDRS), and Hoehn and Yahr staging. The Zarit Burden Inventory was used to assess all primary caregivers. Major demographic and clinical variables were also recorded. Results: A total of 250 subjects with Parkinson's disease were included, of whom 201 had a primary caregiver. In the multivariate analysis, predictors of poor quality of life for a subject with Parkinson's disease were the MDS-UPDRS I score (β = .39, P < .001), MDS-UPDRS II score (β = .21, P < .001), and MDS-UPDRS III score (β = .07, P = .004). Regarding caregiver burden, the MDS-UPDRS II score (β = .54, P = .007) was the most influential factor. Conclusions: The present study shows a relationship between quality of life for the subject with Parkinson's disease and the caregiver's perceived burden. However, the factors that determine each situation appear to be distinct. Resumen: Introducción: La enfermedad de Parkinson impacta en la calidad de vida del sujeto que la presenta, pero también ocasiona una carga para el cuidador. Los factores relacionados con estos efectos incluyen aspectos motores y no motores de la enfermedad, así como características inherentes al cuidador. Métodos: Se evaluó a sujetos con enfermedad de Parkinson mediante los siguientes instrumentos: cuestionario de calidad de vida PDQ-8, escala unificada de la enfermedad de Parkinson de la Sociedad de Trastornos del Movimiento parte i a iv (MDS-UPDRS) y estadio de Hoehn y Yahr (HY). A los cuidadores primarios, se les aplicó el inventario de carga del cuidador de Zarit. Adicionalmente, se registraron las principales variables demográficas y clínicas. Resultados: Se incluyó a 250 sujetos con enfermedad de Parkinson, de los cuales 201 contaban con un cuidador primario. En el análisis multivariado los factores predictores de una peor calidad de vida del sujeto con enfermedad de Parkinson fueron la puntuación de la MDS-UPDRS I (β = 0,39, P < 0,001), puntuación de la MDS-UPDRS II (β = 0,21, P < 0,001) y puntuación de la MDS-UPDRS III (β = 0,07, P = 0,004). En lo que respecta a la carga en el cuidador, la puntuación de la MDS-UPDRS II (β = 0,54, P = 0,007) fue el que más influyó. Conclusiones: El presente estudio muestra una relación entre la calidad de vida del sujeto con enfermedad de Parkinson y la percepción de carga del cuidador. No obstante, los factores que determinan cada una de estas parecen ser distintos. Keywords: Quality of life, Caregiver burden, Primary caregiver, Parkinson's disease, Motor symptoms, Non-motor symptoms, Palabras clave: Calidad de vida, Carga en el cuidador, Cuidador primario, Enfermedad de Parkinson, Síntomas motores, Síntomas no motores